2011
DOI: 10.1021/la201534e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Mono- and Multilayer Films of Polymerizable 1,2-Polybutadiene Using the Langmuir–Blodgett Technique

Abstract: The essence of this study is to apply the Langmuir-Blodgett (LB) technique for assembling asymmetric membranes. Accordingly, Langmuir films of a (further) polymerizable polymer, 1,2-polybutadiene (1,2-pbd), were studied and transferred onto different solid supports, such as gold, indium tin oxide (ITO), and silicon. The layers were characterized both at the air/water interface as well as on different substrates using numerous methods including cyclic voltammetry, impedance spectroscopy, spectroscopic ellipsome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Otherwise, aggregates are formed due to the hydrophobic nature of the polymer. Even though, to our knowledge, the oxidation of PB in Langmuir monolayers has never been addressed, ,, its sensitivity to natural light is not surprising considering the nanometer thickness of the studied layer. Indeed, it has been evidenced that photo-oxidation is a surface phenomenon. , Coquillat et al have highlighted a critical sample thickness (L c = 22 +/– 2 μm) beyond which oxidation is no longer homogeneous leading to an oxidation gradient due to oxygen diffusion …”
Section: Results and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Otherwise, aggregates are formed due to the hydrophobic nature of the polymer. Even though, to our knowledge, the oxidation of PB in Langmuir monolayers has never been addressed, ,, its sensitivity to natural light is not surprising considering the nanometer thickness of the studied layer. Indeed, it has been evidenced that photo-oxidation is a surface phenomenon. , Coquillat et al have highlighted a critical sample thickness (L c = 22 +/– 2 μm) beyond which oxidation is no longer homogeneous leading to an oxidation gradient due to oxygen diffusion …”
Section: Results and Discussionmentioning
confidence: 93%
“…Matmour et al showed the feasibility of cross-linking a triethoxysilane-functionalized PB Langmuir monolayer, through an acid-catalyzed condensation reaction . To our knowledge, only two studies report in situ characterization of a pure PB polymer or oligomer monolayers. , In particular, Hitrik et al investigated the effect of UV-irradiating pure PB monolayers. They showed a significant contraction of the monolayer upon a long UV irradiation reflecting its cross-linking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Due to its unique mechanical properties that originate from the combination of properties of plastic and rubber, sPB reveals a wide range of applications in the elds of bres, lms, moulded articles, and recently has been used as synthetic rubber reinforcing llers. [8][9][10][11][12] Despite this, the inherent shortfall of low surface energy makes sPB display inferior properties with respect to adhesion, toughness, paintability, miscibility and rheological properties. Improving the hydrophilicity and developing functionalized sPB has been the long-term pursuit for scientists.…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated the application of the LB method for the formation of an asymmetric membrane. [8] Specifically, a Langmuir film of polymerizable 1,2-polybutadiene was transferred onto a solid support on which the backbone polymer was grown by graft polymerization.…”
Section: Introductionmentioning
confidence: 99%